How Does District Health Management Emerge Within a Complex Health System? Insights for Capacity Strengthening in Ghana - Heerdegen, Anne Christine Stender; Gerold, Jana; Amon, Samuel; Agyemang, Samuel Agyei; Aikins, Moses; Wyss, Kaspar (Frontiers in Public Health, 2020)
District health managers (DHMs) play a pivotal role in the operation of district health systems in low - and middle income countries, including Ghana. Their capacity is determined by their competencies, but also by the organization and system in which they are embedded. The objective of this paper is to explore how district health management emerges from contextual, organizational and individual factors in order to demonstrate that capacity strengthening efforts at district level need to transcend individual competencies to take on more systemic approaches. Semi-structured interviews (n=21) were conducted to gain insight into aspects that affect district health management in the Eastern Region of Ghana. Interviews were conducted with DHMs from six different districts (n=15), as well as with their superiors at the regional level (n=4) and peers from non-governmental organizations (n=2). A thematic analysis was conducted by using an analytical approach based on a systems thinking approach. Contextual aspects, such as priorities among elected officials, poor infrastructure and working conditions, centralized decision-making, delayed disbursement of funds and staff shortages, affect organizational processes and the way DHMs carry out their role. Enabling organizational aspects that provide DHMs with direction and a clear perception of their role, include positive team dynamics, good relations with supervisors, job descriptions, appraisals, information systems, policies and guidelines. Meanwhile, hierarchical structures, agendas driven by vertical programs and limited opportunities for professional development provide DHMs with limited authority to make decisions and dampens their motivation to perform. The DHMs ability to carry out their role effectively depends on their perception of their role and the effort they expend, in addition to their competencies. In regards to skills and competencies, a need for more holistic management and leadership skills were called for by DHMs as well as by their superiors and peers. To strengthen district health management capacity more systemic approaches are called for. Our findings can provide national policy-makers, donors and researchers with a deeper understanding of factors that should be taken into consideration when developing, planning, implementing, and assessing capacity-building strategies targeted at strengthening district health management.